Implementation of virtual reality in midwifery education: Does it really work? - Nabila Zuhdy; Ari Indra Susanti (Universitas Pendidikan Indonesia, 2025)
Virtual Reality (VR) technology can significantly enhance midwifery education and outcomes by offering immersive and interactive learning experiences. This paper aims to discuss the implementation and prospects of VR training in midwifery education, emphasizing the need for ongoing adoption and development of VR strategies. A literature review was conducted using keywords to identify studies published between 2020 and 2025, sourced from PubMed, BMC, and ScienceDirect. The inclusion criteria specified original research, free full-text articles in English. Seven studies met the requirements, which were analyzed into four themes: the current application of VR in midwifery education, student engagement with VR, the impact and effectiveness of VR on learning outcomes, challenges and limitations of VR, and prospects of VR in midwifery education. Integration of VR in midwifery education offers transformative potential by enhancing traditional teaching methods and improving learning outcomes. VR provides immersive experiences that help students understand complex anatomy and clinical scenarios without real-life risks, boosting engagement, retention, and confidence. Despite obstacles, effective solutions involve collaboration between educators and developers, supported by a robust pedagogical framework. VR should enhance, rather than substitute, traditional methods, and tailoring VR approaches to address changing educational demands will foster the development of more competent healthcare professionals. Abstrak Teknologi realitas virtual (VR) dapat meningkatkan pendidikan kebidanan dan luarannya dengan menawarkan pengalaman belajar yang imersif dan interaktif. Artikel ini bertujuan untuk membahas implementasi dan prospek pelatihan menggunakan VR dalam pendidikan kebidanan, dengan menekankan perlunya adopsi dan pengembangan strategi VR secara berkelanjutan. Tinjauan literatur dilakukan menggunakan kata kunci yang relevan pada studi yang diterbitkan dari tahun 2020 hingga 2025, bersumber dari PubMed, BMC, dan Science Direct. Kriteria inklusi mencakup artikel original berbahasa Inggris dengan teks lengkap gratis. Tujuh studi memenuhi kriteria, yang dikelompokkan menjadi empat tema, yaitu penerapan VR dalam pendidikan kebidanan, keterlibatan mahasiswa dalam pembelajaran dengan VR, dampak dan efektivitas VR pada hasil pembelajaran, tantangan dan keterbatasan VR, serta prospek VR dalam pendidikan kebidanan. Integrasi VR dalam pendidikan kebidanan menawarkan potensi transformasi dengan meningkatkan metode pengajaran tradisional dan memperbaiki hasil pembelajaran. VR menyediakan pengalaman imersif yang membantu mahasiswa memahami anatomi kompleks dan skenario klinis tanpa risiko di dunia nyata, meningkatkan keterlibatan mahasiswa, retensi, dan kepercayaan diri. Meskipun terdapat hambatan, solusi efektif dengan melibatkan kolaborasi antara pendidik dan pengembang, didukung oleh kerangka pedagogis yang kuat. VR seharusnya melengkapi, bukan menggantikan, metode tradisional, dan penyesuaian pendekatan VR untuk memenuhi kebutuhan pendidikan yang berubah akan mendorong pengembangan tenaga kesehatan yang lebih kompeten. Kata Kunci: bidan; pendidikan kebidanan; virtual reality